ANALISIS CORPORATE GOVERNANCE, KARAKTERISTIK PERUSAHAAN DAN KINERJA KEUANGAN TERHADAP PENGHINDARAN PAJAK - Susanty, Meinie; Mevita, Mevita (E-Jurnal Akuntansi TSM, 2024)
The purpose of this study is to obtain empirical evidence regarding the influence of company size, institutional ownership, executive characteristics, Chief Executive Officer (CEO) tenure, profitability, capital intensity and leverage on tax avoidance. The data used in this study are cyclical and non-cyclical companies listed on the Indonesia Stock Exchange from 2020 to 2022. The research sample was selected using a purposive sampling method and produced 198 data from 66 sample companies and analyzed using the multiple regression method. The results of this research show that the variables company size, profitability and leverage have an influence on tax avoidance. While the variables institutional ownership, executive characteristic, Chief Executive Officer (CEO) tenure, and capital intensity have no significant influence on tax avoidance.